How much do means-tested benefits reduce the demand for annuities? - Monika Bütler; Kim Peijnenburg; Stefan Staubli (Center for Economic Studies and ifo Institute (CESifo), 2011)
We analyze the effect of means-tested benefits on annuitization decisions. Most industrialized countries provide a subsistence level consumption floor in old age, usually in the form of means-tested benefits. The availability of such means-tested payments creates an incentive to cash out (occupational) pension wealth for low and middle income earners, instead of taking the annuity. Agents trade-off the advantages from annuitization, receiving the wealthenhancing mortality credit, to the disadvantages, giving up 'free' wealth in the form of means-tested supplemental benefits. We find that the availability of means-tested benefits can reduce the desired annuitization levels substantially. Using individual level data, we show that the model's predicted annuitization rates as a function of the level of pension wealth are roughly consistent with the cash-out patterns of occupational pension wealth observed in Switzerland.
Keywords: D81; D91; G23; J26; 330; means-tested benefit; occupational pension; annuity; life-cycle model